At the Origins of Welfare State? Social Expenses in the Budgetary Policy in the Second Polish Republic - Grata, Paweł (Studia Historiae Oeconomicae, 2017)
In the period of the Second Polish Republic, social policy became an important field of activity for public authorities. It was distinguished by a high level of awareness of the prevalent social problems, progressive legislation, and advanced management. The only missing element was sufficient financing. In the budgetary policy of the Second Polish Republic, social expenses were of minor importance. For the most part of the period, they amounted to approximately 3% of all expenses. The Ministry of Social Care was underfunded, which was evident in nearly every aspect of its activity. Hence, if one wonders if the origins of the Polish welfare state can be traced back to the Second Polish Republic, the answer must be “no”. Although extra funds (spent on tackling unemployment, pensions, or disability benefits) were found outside of the ministerial budget, the arguments presented in this article only confirm the hypothesis presented above.